Environmental determinants of active travel in youth: A review and framework for future research - Jones Andrew P; Panter Jenna R; van Sluijs Esther MF (BMC, 2008)
Abstract Background Many youth fail to meet the recommended guidelines for physical activity. Walking and cycling, forms of active travel, have the potential to contribute significantly towards overall physical activity levels. Recent research examining the associations between physical activity and the environment has shown that environmental factors play a role in determining behaviour in children and adolescents. However, links between the environment and active travel have received less attention. Methods Twenty four studies were identified which examined the associations between the environment (perceived or objectively measured) and active travel among youth aged 5-18 years. Findings were categorised according to the location of the environmental measure examined; attributes of the neighbourhood, destination and the route between home and destination. Results Results from the reviewed studies indicated that youth active travel is positively associated with social interactions, facilities to assist active travel and urban form in the neighbourhood as well as shorter route length and road safety en-route. A conceptual framework is presented which highlights the associations between active travel behaviours and environmental factors, drawing upon both existing and hypothesised relationships. Conclusion We provide a review of the available literature and present a novel theoretical framework that integrates the environment into the wider decision making process around travel choices for children and adolescents. Further work should explore associations where gaps in understanding have been identified, and account for the main moderators of behaviour so hypothesised associations can be confirmed.